Hubungan Bersyukur dengan Prososial Pelaku UMKM Pada Masa Pandemi Covid 19 di Wilayah Karesidenan Surakarta - Siti Maolida Andalis (Journal of Psychology and Treatment, 2021)
The Covid-19 pandemic has had an impact on Micro, Small and Medium Enterprises (MSMEs). Prosocial behavior from fellow business perpetractor was important to overcome these impacts. Gratitude provides positive emotions so that it can encourage individuals to behave well and lead to prosocial behavior. The purpose of this study was to examine the relationship between gratitude and prosocial behavior in MSME perpetractor during the covid 19 pandemic. The sample in this study was 100 MSME perpetractor with purposive sampling using a purposive sampling technique. Data were collected using a gratitude scale and prosocial behavior. Data analysis was performed using product moment correlation analysis. The results of this study indicate the value of r (correlation coefficient) of 0.649 and a significance value (p) of 0.000 (p <0.05). The conclusion in this study is that there is a significant positive relationship between gratitude and prosocial behavior.